Teaching Strategies Used in Vocabulary In “Communication” Module for First year Students at Salahaddin University-Erbil - Nazenin Shekh Muhemad Bapir; Alan Anwar Hasan (Zanco Journal of Humanity Sciences)
The present paper, entitled “Teaching strategies used in vocabulary in “Communication” module for first year students at Salahaddin University-Erbil” outlines the basic strategies for teaching vocabulary in communication module. The aim is to investigate and identify the best strategies for teaching vocabulary that can be used in EFL classrooms when teaching communication.